Impoliteness Strategies Used by Haters of Lady Gaga in Her Instagram Comments - Sari, Indah Permata; Rangkuti, Rahmadsyah; Ganie, Rohani (Universitas Teuku Umar, 2020)
This research investigates impolite utterances by haters of Lady Gaga on her instagram comments through pragmatic study. The object is to find out the types and functions of impoliteness strategies. This research was conducted by descriptive qualitative design. The data were words, phrases and clauses. The sources of data were comments of Lady Gaga haters in a photo which posted on January 10th 2019 on her instagram account. The findings of the study show that: (1) There are four types of impoliteness strategies found on comments of Lady Gaga’s instagram namely positive impoliteness, bald on record impoliteness, negative impoliteness, and sarcasm. Positive and negative impoliteness are the high percentage strategies while sarcasm is the lowest frequency strategy to occur in this research. (2) There are three functions of impoliteness strategies are used by haters of Lady Gaga on her instagram comments. They are entertaining impoliteness, affective impoliteness, and coercive impoliteness.